The Tragedy of Contract and the Naturalistic Fallacy at the Workplace - Bae, Jonghoon (Seoul Journal of Business, 2020)
This study concerns business ethics. In particular, this study is a critical review of consequentialist ethics, namely, the tragedy of contract, which underlies managerial practices at the workplace and which equates empirical flourishing with behavioural morality, an instance of the naturalistic fallacy. It shows that the application of consequentialist ethics in the corporate world is fundamentally flawed such that empirical consent, a key element of consequentialism, obtains at the expense of the weaker party to an exchange and that consent-based contracting both precludes the autonomy of the subject and paradoxically invites the influence of the third-part expert. The alternative practice is addressed with respect to the tradition of social contract, which places public ordering over private ordering.